The Correlation between Masculinity and Smoking Behavior among Adolescent in Surabaya - Setho Hadisuyatmana (Journal of Global Pharma Technology, 2020)
Smoking behavior is one of the risky health behaviors adopted by adolescents in Indonesia. The behavior was commonly recognized as a masculine among male adolescents. The label of man identity called masculinity influences this condition. This study investigated the association of masculinity as ideology, masculinity norms, and gender role conflict and its correlation with smoking behavior in male adolescents who lived in Surabaya. This study used a descriptive correlative method and involved 314 adolescent males aged 15-18 years old in Surabaya as participants. We employed univariate analysis to identify predictors, including the ideology of masculinity (MNRI-SF), masculinity norms (CMNI-46), and gender role conflict (GRCS-I); and a dependent variable: male adolescents’ smoking behavior. The data were collected electronically, following waived written consents. Bivariate analyses were conducted to investigate each of the predictor's questionnaires and dependent variables using chi-square with the level of significance of p<0.05. Adolescents as participants in this study have low levels of ideological masculinity, high norms of masculinity and gender role conflict in the moderate category. The results indicated that ideology masculinity, masculinity norms, and gender role conflicts are positively associated with smoking behavior (p=0,001, p=0,029, and p=0,001 respectively). The findings of this study suggested that smoking behavior was constructed as an element to the idea of masculinity in the perspective of male adolescents in Surabaya, despite the available warning to prevent the circulation of tobacco products to adolescents. Thus, this study recommends the need for reinvention around tobacco-products circulation as not to involve the youth. Keywords: Adolescent, Gender role conflict, Masculinity, Smoking behavior.